The Stability and Repeatability of Spontaneous Sympathetic Baroreflex Sensitivity in Healthy Young Individuals - Hissen, Sarah L.; Sayed, Khadigeh El; Macefield, Vaughan G.; Brown, Rachael; Taylor, Chloe E. (Frontiers in Neuroscience, 2018)
Spontaneous sympathetic baroreflex sensitivity (BRS) is a valuable tool for assessing how well the baroreflex buffers beat-to-beat changes in blood pressure. However, there has yet to be a study involving appropriate statistical tests to examine the stability of sympathetic BRS within an experimental session and the repeatability between separate sessions. The aim of this study was to use intra-class correlations, ordinary least products regression, and Bland-Altman analyses to examine the stability and repeatability of spontaneous sympathetic BRS assessment. In addition, the influence of recording duration on values of BRS was assessed. In eighty-four healthy young individuals (49 males, 35 females), continuous measurements of blood pressure, heart rate and muscle sympathetic nerve activity (MSNA) were recorded for 10 min. In a subgroup of 13 participants (11 male, 2 female) the measurements were repeated on a separate day. Sympathetic BRS was quantified using MSNA burst incidence (BRSinc) and total MSNA (BRStotal) for the first 5-min period, the second 5-min period, and a 2-min segment taken from the second 5-min period. Intra-class correlation coefficients indicated moderate stability in sympathetic BRSinc and BRStotal between the first and second 5-min periods in males (BRSinc r=0.63, BRStotal r=0.78) and females (BRSinc r=0.61, BRStotal r=0.47) with no proportional bias, but with fixed bias for BRSinc in females. When comparing the first 5-min with the 2-min period (n=76), the intra-class correlation coefficient indicated poor to moderate repeatability in sympathetic BRSinc and BRStotal for males (BRSinc r=-0.01, BRStotal r=0.70) and females (BRSinc r=0.46, BRStotal r=0.39). However, Bland-Altman analysis revealed a fixed bias for BRStotal in males and proportional bias for BRStotal in females, with lower BRS values for 5-min recordings. In the subgroup, intra-class correlations indicated moderate repeatability for measures of BRSinc (9 male, 2 female, r=0.63) and BRStotal (6 male, 2 female, r=0.68) assessed using 5-min periods recorded on separate days. However, Bland-Altman analysis indicated proportional bias for BRSinc and fixed bias for BRStotal. In conclusion, measures of spontaneous sympathetic BRS are moderately stable and repeatable within and between testing sessions in healthy young adults, provided that the same length of recording is used when making comparisons.